2023
DOI: 10.1093/jas/skad129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating phenotypes associated with heat tolerance and identifying moderate and severe heat stress thresholds in lactating sows housed in mechanically or naturally ventilated barns during the summer under commercial conditions

Abstract: An accurate understanding of heat stress (HS) temperatures and phenotypes that indicate HS tolerance is necessary to improve swine HS resilience. Therefore, the study objectives were 1) to identify phenotypes indicative of HS tolerance, and 2) to determine moderate and severe HS threshold temperatures in lactating sows. Multiparous (4.10 ± 1.48) lactating sows and their litters (11.10 ± 2.33 piglets/litter) were housed in naturally ventilated (n = 1,015) or mechanically ventilated (n = 630) barns at a commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“… 0.57 ± 0.12 Ear length EL The ear length was calculated using a photo taken with a digital camera, where a 10.2 × 15.2 cm grid card containing 1 cm × 1 cm squares was placed next to the sows’ ear. 0.53 ± 0.12 a Data collection protocols have been described by Johnson et al [ 10 ] and Freitas et al [ 11 ] b These heritability estimates were previously reported by Freitas et al [ 11 ] …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“… 0.57 ± 0.12 Ear length EL The ear length was calculated using a photo taken with a digital camera, where a 10.2 × 15.2 cm grid card containing 1 cm × 1 cm squares was placed next to the sows’ ear. 0.53 ± 0.12 a Data collection protocols have been described by Johnson et al [ 10 ] and Freitas et al [ 11 ] b These heritability estimates were previously reported by Freitas et al [ 11 ] …”
Section: Resultsmentioning
confidence: 91%
“… a Data collection protocols have been described by Johnson et al [ 10 ] and Freitas et al [ 11 ] b These heritability estimates were previously reported by Freitas et al [ 11 ] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once again, this pattern may be related to the presence of GxE interaction effects that the model is able to capture when the temperature is above 10°C and not when it is below 10°C. Nevertheless, this relationship should be evaluated in further studies, and the results should be compared with predictions made using in-barn climatic data, which remains the gold standard for the evaluation of HS conditions in pig farms (Freitas et al, 2023;Johnson et al, 2023).…”
Section: Validation Metricsmentioning
confidence: 99%